Clinical Pathway Sebagai Solusi Keberlanjutan JKN di Indonesia: Systematic Review - Septiana, Septiana; Soekiswati, Siti; Ichsan, Burhannudin (Jurnal Ekonomi Kesehatan Indonesia, 2025)
The National Health Insurance (JKN) program is threatened with a deficit and potential default in 2026 due to inefficiency and the risk of fraud in healthcare facilities. In the context of JKN, which uses a package system (INA-CBG), Clinical Pathway (CP) is a strategic instrument within the JKN system that has dual benefits for both Payers (BPJS Kesehatan) and Providers (Hospitals). For BPJS Kesehatan, CP primarily functions to ensure service quality and prevent undertreatment fraud, the practice of reducing services to benefit hospitals. This prevention ultimately achieves cost efficiency in the JKN program by avoiding payment of complication claims and readmissions arising from substandard services. On the hospital side, CP helps control real cost effectiveness (cost) to maintain efficiency. High CP compliance can reduce inefficiencies (e.g., resource overutilization), thereby reducing the gap in hospital losses under the INA-CBG package system. This indirectly reduces the incentive for hospitals to commit fraud. This study aims to synthesize comprehensive evidence regarding the impact of CP compliance on cost efficiency (Hospital Cost) from a provider perspective and its impact on the sustainability of JKN. The method used was a Systematic Review based on the PRISMA framework, analyzing 28 articles from hospitals in Indonesia (2016-2025) that discussed the impact of CP on costs and/or Length of Stay (LOS) as well as the quality of clinical services. During the snowballing and abstract screening stages, we also found that compliance was an important variable measured by the studies we reviewed. The results show that the level of CP compliance in Indonesia remains low; 80% of hospitals have compliance below 50%, which triggers service variations and the risk of fraud. CP compliance is consistently positively correlated with reduced Hospital Costs (thus increasing internal hospital efficiency) and accelerated LOS. In addition to cost efficiency, CP has also been shown to improve the quality of clinical services by reducing complications (SSI: Surgical Site Infection) and reducing the risk of readmissions. In conclusion, CP is an essential dual solution; improving CP compliance is a fundamental key to balancing hospital cost efficiency without sacrificing quality, while simultaneously safeguarding the financial sustainability of the JKN Program from the burden of unnecessary complication claims.